Genotypes Environment Interaction for Seven-Week Body Weight of Poultry Breeds - Rabab Fathi Eldarnawi; Salem Ali Bozrayda; Fathi Ali Attia (مجلة المختار للعلوم, 2021)
This study investigated the interaction of poultry breeds x environment under Libyan conditions and compared with that under a temperate zone for a seven-week bodyweight. Data were collected from the weekly records during the rearing period for three grandparent breeds Hypeco, Avian, and Shaver, at Ghotsultan and Tawargha from 1986 to 2001. Traits studied were daily feed consumption, cumulative feed consumption, body weight, feed consumption ratio, and mortality. The model used to analyze the data for the rearing period was included: overall mean, the effects of location, breeds within the year, the flock, seasons, and the age.  Breeds x seasons and breeds x locations interaction were found in weight at seven weeks of age. Avian showed consistent performance under both hot and cold seasons for seven weeks bodyweight (1308.3-1304.4g), while Hypeco and Shaver perform well under cold seasons but not in hot seasons in Libya.  Hypeco and Avian perform less under Libyan conditions compared to temperate zone conditions, whereas Shaver performs a little better under Libyan conditions.  In addition, Hypeco had lower mortality, which was about 2.84%, compared with Avian 3.0%, and Shaver, which was 4.38% during the rearing period. This study could conclude that the performance of grandparent breeds under Libyan conditions was affected by weather and management.